Structures argumentales de prédicats N Prép N. Emplois réciproques et non réciproques - Kaliska, Agnieszka K. (Studia Romanica Posnaniensia, 2019)
The purpose of this article is to provide the lexical analysis of predicates such as face à face (‘face to face’) and côte à côte (‘side by side’), which are generally reciprocal and symmetric. Some of them are also used in an unusual way, that is, the structures in which they appear do not meet the requirements set for symmetric constructions. This imbalance, as we will show, has for the origin a semantic difference between the arguments x and y which must belong to the same semantic class if we want them to be in a symmetric relation. The question of semantic similarity within the argument structures is thus of greater importance for the semantic completeness of the reciprocal predicates. The question will be for us to recognize if, when a semantic difference occurs, we would have to deal with different (non reciprocal) meanings and if so how to describe them.